Unveiling the functional connectivity of astrocytic networks with AstroNet, a graph reconstruction algorithm coupled to image processing - L. Zonca; F. C. Bellier; G. Milior; P. Aymard; J. Visser; A. Rancillac; N. Rouach; D. Holcman (Communications Biology)
Abstract Astrocytes form extensive networks with diverse calcium activity, yet the organization and connectivity of these networks across brain regions remain largely unknown. To address this, we developed AstroNet, a data-driven algorithm that uses two-photon calcium imaging to map temporal correlations in astrocyte activation. By organizing individual astrocyte activation events chronologically, our method reconstructs functional networks and extracts local astrocyte correlations. We create a graph of the astrocyte network by tallying direct co-activations between pairs of cells along these activation pathways. Applied to the CA1 hippocampus and motor cortex, AstroNet reveals notable differences: astrocytes in the hippocampus display stronger connectivity, while cortical astrocytes form sparser networks. In both regions, smaller, tightly connected sub-networks are embedded within a larger, loosely connected structure. This method not only identifies astrocyte activation paths and connectivity but also reveals distinct, region-specific network patterns, providing new insights into the functional organization of astrocytic networks in the brain.